Dissolving microneedles for enhanced local delivery of capsaicin to rat skin tissue. (28th May 2017) - Ito, Yukako; Kobuchi, Shinji; Inoue, Genta; Kakumu, Eisaku; Aoki, Miki; Sakaeda, Toshiyuki; Takada, Kanji
Abstract: Capsaicin-loaded dissolving microneedles (DMNs) were prepared to investigate the analgesic effect of capsaicin on the skin. The dimensions of each microneedle (MN) were as follows: diameter of the basement, 17 mm; length, 500 μm; and width, 300 μm. The average capsaicin content in the DMNs loaded with a low and high dose of capsaicin was 8.8 ± 0.5 mg and 12.5 ± 0.4 mg. Almost all the capsaicin, 99.3 ± 4.1% and 99.7 ± 2.2% for low-dose and high-dose DMNs were released within 20 min. High amounts of capsaicin were recovered with 102.8 ± 0.1% of capsaicin after storage at 23 °C for 90 days. The pharmacological activity of capsaicin DMNs was compared to that of capsaicin cream as a positive control, by measuring the idiospasm of depilated rat skin. The time required to achieve 50% idiospasm suppression was 26.3 ± 1.9 min and 53.0 ± 2.3 min for low-dose and high-dose DMNs. A pharmacokinetic study showed high tissue capsaicin levels of 660.2 ± 120.6 and 1805.3 ± 218.1 μg/g wet weight for low-dose and high-dose DMNs at 5 min after administration. The results suggest that DMNs could exert a rapid local analgesic action on the skin.